PENGARUH JENIS PELARUT PADA METODE MASERASI TERHADAP KARAKTERISTIK EKSTRAK Sargassum polycystum - Savitri, Irena; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Sargassum polycystum is one of the type of brown algae that has potential as an antioxidant and natural dye. The aims of this study were to know the effect of solvent type to the characteristic of Sargassum polycystum extract on maseration method and to determine the best solvent for Sargassum polycystum extract on total phenol, total carotenoids, and color intensity. The experiment in this study used Randomized Block Design with single factor. The solvent’s type factor consisting of 5 solvent, namely methanol, ethanol, acetone, isopropyl alcohol, and ethyl acetate. The experiments are grouped into 4 groups based on the time of implementation, in order to obtain 20 units of experiments. Objective variables observed are rendement, total phenol content, total carotenoids content, and color intensity. The result showed that the type of solvent affected significantly (P<0,01) on rendement, total phenol, total carotenoid, brightness level (L*), and yellowish level (b*), but did not affect on redness level (a*). Ethyl acetate is the best solvent to  produce Sargassum polycystum extract with 0,91% rendemen, 2,61 mgGAE/100g total phenol content, total carotenoid content about 0,23%, and color intensity with brightness level (L*) 5,17, redness level (a*) -3,00 and yellowish level (b *) 37,28. Keywords: solvent, extract characteristic, Sargassum polycystum.